Industry Relevance in Management Education through Value Additions - Harshad B. Salvi, Raju Varghese, Dr. Rajesh Pahurkar (International Journal of Advanced Science and Technology, 2020)
MBA education throughout the world generically follows a similar format. There is a lot of differentiation in the management education offering, but mostly at the institution level and never at the content level. Most of the premier B-schools, University run schools and privately owned institutions are actually very similar in the nature of the contents being offered in their various institutions. A niche differentiation is created through targeting certain select areas like Petroleum Management for the School of Petroleum Management, Gandhinagar or MICA, Ahmadabad for Communication Management or IRMA for Rural Management etc. Even in these select courses, the primary offerings or core subjects / courses remain the same and the distinction is created in the various electives. This seems to be a generic format not only in India, but the world over as far as management education is concerned. Is this type of a management education relevant? For e.g. If there is a pure science subject like Chemistry or Physics, the manner in which it is dealt with will be similar the world over as the subject contents remain same. Does the same logic apply for management education? The scope of the paper is restricted to exploring the various value additions in management education, focusing on the content part rather than on the frills or the differentiation part. The focus is on innovative pedagogies, indigenous cases, and radical methods of making management education relevant for the industry, for which it is aimed at w. r. t the business environment. “If the rate of change on the outside exceeds the rate of change on the inside, the end is near.” - Jack Welch